Síntese verde e versátil de calcogenol ésteres e avaliação da atividade antibacteriana - Silva, Rafael Santos da (2014)
The present work aims the synthesis of chalcogenoesters, by a green and versatile methodology, using low cost and non-toxic reagents, as well as the biological activity of this kind of compounds, as antibacterial agents. By a simple method, employing a small amount of solvent to the synthesis and separation, was performed the reaction between different acyl chlorides (1ae) and diorgaryl diselenides, in the presence of HCl/Zn0, using acetone as solvent, resulting in synthesis of 24 chalcogenoesters (compounds 2a-j, 3a-i e 4a-d), in moderate to excellent yields. The proposed synthesis showed to be high modular, allowing change a sort of different groups at specific molecule positions, besides the possibility to synthesize some examples of Sulfur and Selenium protecting groups (Fmoc and p-Nitrobenzoyl), compounds 4a, 2h, 3a, 3c, 3d, 4b and 3h, which the protocol was efficient. Furthermore, an investigation about the biological activity of the synthesized compounds was performed against Gram-Positive and Grandnegative bacteria strains of high clinical interest. Where the effectiveness of the chalcogenol esters, demonstrated against Klebsiella pneumoniae and Pseudomonas aeruginosa.